Customer Retention Strategy Through Customer Satisfaction and Customer Loyalty: The Study on Traveloka Loyalty Program - Komalasari, Fiona Poetri; Budiman, Surya Fajar (Jurnal Penelitian Pariwisata, 2018)
Customer loyalty and customer retention is very closely related, customer loyalty stopped customer churn and strengthen the customer retention. The primary aim of retention strategy is to build a strong customer base and to prevent them from drifting towards other competitor. Traveloka as a travel supplier company, is the leading online travel agent in Indonesia. The customers satisfaction has an average score of 3,91. The result signify that Traveloka is successful in obtaining its customers’ satisfaction The customer loyalty has an average score of 4,04. Traveloka has managed to reach customer loyalty Traveloka customer satisfaction and loyalty are obtained as presented through chapter IV that the average is 3,97. In this research, Traveloka customer retention strategy using loyalty program is proven to be effective.